Crisis of conservatism? the Republican Party, the conservative movement and American politics after Bush - Aberbach, Joel D.; Peele, Gillian, 1949- (New York ; Oxford : Oxford University Press, 2011)
The Crisis of Conservatism gathers a broad range of leading scholars of conservatism to assess the current state of the movement in the U.S. and where it is most likely headed in the near future.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Republican Party (U.S. : 1854- ); Conservatism -- United States; Political parties -- United States; Political culture -- United States; United States -- Politics and government